Tata Kelola Pengembangan Objek Wisata Pantai Cemara Indah Dalam Menarik Wisatawan Di Desa Gosong Telaga Selatan Kecamatan Singkil Utara Kabupaten Aceh Singkil - Berliyanta K. Samosir; Tio RJ. Nadeak; Maringan Sinambela; Rusmauli Simbolon; Elvri Teresia Simbolon (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The aim of this research is to determine the management of the development of the beautiful Pine Beach tourist attraction in attracting tourists. This research uses a qualitative research method with a descriptive approach and data collection techniques through observations, interviews with informants and documentation. The discussion regarding governance at the Cemara Indah Beach tourist attraction is the result of facts and data in the field. Adapted to the theory that researchers use, namely from the Department of Tourism and Creative Economy of the Republic of Indonesia, which in this theory provides components in managing the tourism sector, where tourism governance is a process of planning, organizing, supervising and evaluating tourism activities. carried out by the government and related stakeholders to achieve sustainable tourism goals. From the research results, it can be concluded that the management and development of the Cemara Indah Beach tourist attraction in Gosong Telaga Selatan Village involves various aspects including organization, planning, implementation, supervision and evaluation. The management, especially the management, shows commitment in carrying out their duties by focusing on management efficiency, collaboration with various related parties, and a deep understanding of visitor needs.